The Nucleated Thrombocytoid Cells. I. Electron Microscopic Studies on Chicken Blood Cells - Janzarik, H; Morgenstern, E (Thrombosis and Haemostasis, 1979)
By analyses of electron micrographs it was investigated whether nucleated thrombocytes of chickens described in the literature can be differentiated from lymphoid cells with sufficient certainty as an independent cell system. The result was negative. The mixture of lymphoid cells and so-called thrombocytes investigated was extremely polymorphous and, unlike mammalian platelets, proved to be one cell system containing younger and more mature cells. In the literature cells with signs of overmaturity or activation are designated as thrombocytes. Our studies suggest that a genuine thrombocyte system of chickens and other birds is not existent. The cells hitherto considered as nucleated thrombocytes seem to belong to the lymphoid system.